Analisis dan Pengembangan Sumber Daya Manusia di Perum Bulog Subdrive Surabaya Utara (Jurnal Manajemen Kreatif dan Inovasi, 2025)
The development of human resources (HR) is crucial for achieving organizational goals, particularly in the competitive food sector. This research analyzes HR management at Perum Bulog Subdrive Surabaya Utara, identifying strengths and weaknesses through a qualitative approach. Interviews and documentation reveal strong workforce quality and structured training programs as key strengths. However, challenges such as low motivation, communication gaps, and resource limitations hinder effectiveness. Opportunities arise from technological advancements and increasing market demand, while threats include intense competition and economic uncertainty. The findings suggest practical recommendations for enhancing HR development strategies, emphasizing the need for improved internal communication, employee engagement, and leveraging technology in training to boost overall organizational performance